Technique and surgical outcomes of mesenterization and intra-operative neural monitoring to reduce recurrent laryngeal nerve paralysis after thoracoscopic esophagectomy: A cohort study. (August 2018) - Kobayashi, Hiroyuki; Kondo, Masato; Mizumoto, Motoko; Hashida, Hiroki; Kaihara, Satoshi; Hosotani, Ryo
Abstract: Background: Because the thoracic esophageal carcinoma has a high metastatic rate to the upper mediastinal lymph nodes, especially along the recurrent laryngeal nerves (RLN), it is crucial to perform a complete lymphadenectomy along the RLN without complications. Although intraoperative neural monitoring (IONM) during thyroid surgery has gained widespread acceptance as a useful tool for visual nerve identification, utilization of IONM during esophageal surgery has not become common. Here, we describe our procedures, focusing on a lymphadenectomy along the RLN utilizing the IONM. Methods: Eighty-seven patients who underwent prone esophagectomy between December 2009 and September 2017 were included in this study. We divided patients into two groups: neural monitoring group (Nm, n = 31) and conventional method group without IONM (Cm, n = 56). We first dissect around the esophagus, preserving the membranous structure; mesoesophagus, which contains tracheoesophageal artery; RLN; and lymph nodes (mesenterization). In Nm group, we next identify the location of the RLN, which runs in the mesoesophagus using IONM before visual contact. Next, we perform lymphadenectomy around the RLN, preserving the nerve itself. Early surgical outcomes were retrospectively compared between two groups. Results: In all 31 cases in the Nm group, we detected the location of the RLN before the visual contact. The sensitivity and specificity of the IONM to detect the RLN paralysis were 67% and 96%, respectively. Postoperative RLN paralysis was observed in 3 cases in the Nm group (9.7%), which was lower than that in the Cm group (32.1%, p = 0.03). Clavien-Dindo grade 2 and over aspiration were seen in 2 (Nm, 6.5%) and 16 (Cm, 28.6%) cases (p = 0.01), respectively. The postoperative hospital stay was shorter in the Nm group (22 days, median) than in the Cm group (39 days, median, p = 0.0002). The number of dissected mediastinal lymph nodes was similar in both groups (25 vs. 20, median, p = 0.12). Conclusions: The combination of IONM and the concept of the mesoesophagus have substantial advantages in allowing accurate and safe mediastinal lymphadenectomy during prone esophagectomy. Highlights: Intra-operative nerve monitoring significantly reduced recurrent laryngeal nerve paralysis in esophageal cancer surgery. Our data demonstrated shorter postoperative hospital stay as a result of lower rate of postoperative complications. The concept of mesoesophagus might be useful for preventing postoperative recurrent laryngeal nerve paralysis.